2017
DOI: 10.1186/s12872-017-0500-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender based differences in drug eluting stent implantation - data from the German ALKK registry suggest underuse of DES in elderly women

Abstract: BackgroundObservational studies suggest there are gender based differences in the treatment of coronary artery disease, with women receiving evidence based therapy less frequently than suggested by current guidelines. The aim of our study was to evaluate gender based differences in the use of DES.MethodsWe analysed prospectively collected data from 100704 stent implantations in the PCI registry of the ALKK between 2005 and 2009.ResultsThe usage of DES increased from 16.0 to 43.9%. Although women had smaller ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Limited studies had also revealed that very elderly female ACS patients had received significantly less invasive angiography and timely revascularization [ 12 , 13 ] for higher mortality rates [ 12 , 14 ]. Furthermore, very elderly women treated with PCI for ACS were often excluded from large international clinical trials [ 15 , 16 ]. As a result, there are less clinical studies and clinical experiences of PCI procedure in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies had also revealed that very elderly female ACS patients had received significantly less invasive angiography and timely revascularization [ 12 , 13 ] for higher mortality rates [ 12 , 14 ]. Furthermore, very elderly women treated with PCI for ACS were often excluded from large international clinical trials [ 15 , 16 ]. As a result, there are less clinical studies and clinical experiences of PCI procedure in this population.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Furthermore a tendency to use less effective treatment in female relative to male patients with CAD has been reported. [ 9 ] As consequence, treatment decisions are frequently based on overall outcomes. This is also the case for the evaluation of coronary stents.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused only on gender [ 17 , 18 ]; therefore, we investigated the relationship between coronary vessel sizes and age, DM, LVEF, renal dysfunction, and the clinical presentation of myocardial ischemia. Before coronary intervention, interventional cardiologists have several preconceptions regarding elderly patients [ 20 ] and/or patients with DM that they have considerably smaller coronary vessels than other patients. Our findings were consistent with those observed in our practical experience.…”
Section: Discussionmentioning
confidence: 99%